Efektivitas Pembinaan Keagamaan kepada Narapidana yang Melakukan Kejahatan di Rumah Tahanan Negara (RUTAN) Kelas IIB Banda Aceh - Iqbal, M.; Nur, Muhammad; Fazzan, Fazzan; Rahmah, Siti (Journal of Dual Legal Systems, 2025)
This research aims to analyze the implementation and effectiveness of religious guidance for inmates at the Class IIB Banda Aceh State Detention Center (RUTAN), as well as the challenges faced in its application. Using a qualitative method with an empirical juridical approach, data were collected through interviews, observations, and documentation involving correctional officers and inmates. The results indicate that religious guidance is conducted through structured programs such as religious lectures, Qur’an literacy and recitation classes, worship habituation, and Islamic holiday commemorations. These programs have shown significant impact on inmates, particularly in improving their ability to read the Qur’an, fostering religious awareness, and encouraging positive behavioral changes that support their reintegration into society. Nevertheless, several obstacles were identified, including the limited number and competence of officers, insufficient facilities, and varying levels of inmates’ motivation and awareness. Despite these challenges, the religious guidance programs at RUTAN Class IIB Banda Aceh are considered effective in promoting spiritual development and moral improvement among inmates. The study concludes that religious guidance plays an essential role in correctional efforts, not only to fulfill inmates’ spiritual rights but also to prepare them to become law-abiding citizens after their release. Strengthening human resources, improving facilities, and enhancing supervision are recommended to optimize the effectiveness of future programs. [Penelitian ini bertujuan untuk menganalisis pelaksanaan dan efektivitas pembinaan keagamaan bagi narapidana di Rumah Tahanan Negara (RUTAN) Kelas IIB Banda Aceh, serta mengidentifikasi kendala yang dihadapi dalam penerapannya. Penelitian menggunakan metode kualitatif dengan pendekatan yuridis empiris, melalui wawancara, observasi, dan dokumentasi terhadap petugas pemasyarakatan dan narapidana. Hasil penelitian menunjukkan bahwa pembinaan keagamaan dilaksanakan melalui program ceramah keagamaan, baca tulis Al-Qur’an dan Iqra’, pembiasaan ibadah, serta peringatan hari besar Islam. Program ini dinilai efektif karena mampu meningkatkan kemampuan membaca Al-Qur’an, menumbuhkan kesadaran beragama, dan mendorong perubahan sikap positif pada narapidana sehingga lebih siap untuk kembali ke masyarakat. Namun demikian, terdapat sejumlah kendala yang dihadapi, antara lain keterbatasan jumlah dan kompetensi petugas, fasilitas yang belum memadai, serta tingkat motivasi dan kesadaran narapidana yang beragam. Meskipun demikian, pembinaan keagamaan di RUTAN Kelas IIB Banda Aceh tetap berperan penting dalam proses rehabilitasi narapidana, baik sebagai upaya pemenuhan hak spiritual maupun pembentukan pribadi yang bermoral. Penelitian ini menyimpulkan bahwa penguatan sumber daya manusia, peningkatan sarana prasarana, serta pengawasan yang lebih optimal diperlukan untuk mendukung keberlanjutan dan efektivitas pembinaan keagamaan di masa mendatang.]